Libras como interface no ensino de funções matemáticas para surdos : uma abordagem a partir das narrativas - Silva, Iramí Bila da (2016)
This dissertation aims to describe the narratives in Libras of the personal experience of deaf students in the mathematics classes of the 9th year of Elementary School. In order to investigate them, the proposals of Labov (1967), (1997) and Perroni (1992), who see the narrative as a method of recapitulating linguistically past experiences, were taken as theoretical basis. According to Bruner (1991), Kenski (1994) and Cunha (1997), it is proposed the didactic feasibility of narratives because they are considered verisimilantes the reality of teaching and full of meanings and reinterpretations. In order to make this research feasible, it was primarily aimed at investigating the narratives in Libras during the process of learning related function for deaf students of the 9th year of Elementary School. Specific objectives were also articulated, namely to recognize the probable learning difficulties during the affine function classes, to identify the possible aspects of the narratives that help in the understanding of these contents and to verify the potential mathematical properties of the related function content. Before the objectives, methodologically, we chose a case study, with the techniques of observation and interview for data collection based on Gil (2008) and Chizzotti (1998). For analysis and interpretation, we used the technique of the enunciation analysis that is part of the set of techniques called Content Analysis (BARDIN, 2011). From the analysis, it was noticed that, in addition to the narratives of the content of related function, the collected data addressed other contents: the narratives on the delta discriminant expression, parabolas and quadratic function. It was also found that it is an indispensable condition for the deaf student to appropriate the teaching situation so that he can use his own procedures from the representation he makes of the situation, since significant mathematical representations help in understanding and clarifying the properties and mathematical concepts.